Scenarios and distributional implications of a household wealth tax in Ireland - Martina Lawless; Donal Lynch (The Economic and Social Research Institute (ESRI), 2016)
This paper uses recently available information on the composition of household assets and liabilities to examine the impact of a tax on household wealth in Ireland under a wide range of assumptions on how such a tax might be designed. We compare results based on models of existing taxes on household wealth across Europe and a number of hypothetical scenarios to illustrate how the results are affected by varying qualifying thresholds or asset exemptions. We present revenue estimates and calculations for the percentage of households that would be liable for different qualifying thresholds, tax rates and exemptions for specific assets, such as the household main residence and farms. For each scenario, we further examine characteristics of affected households in terms of their income decile and demographic characteristics. Due to the imperfect correlation between income and wealth, we find that in almost every scenario, a non-negligible proportion of the tax would be collected from households in the lowest income deciles.
Keywords: 330